Peningkatan Kompetensi Wakil Ketua Bidang Anggota Koperasi Kelurahan Merah Putih Kota Surabaya Dalam Kegiatan Sosialisasi dan Bimbingan Teknis - Anindya Novianingtyas, Tyara; Kartika Pertiwi, Tri (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
The establishment of 153 Red and White Subdistrict Cooperatives in the city of Surabaya in response to Presidential Instruction No. 29 of 2025 faced the main challenge of a lack of understanding and preparedness among administrators, particularly deputy chairpersons for membership, due to the rapid and sudden nature of the process. Socialization and technical guidance activities were carried out in stages from November 3 to 12, 2025, at the Siola Convention Hall, Surabaya, involving deputy chairpersons for membership from all Red and White Subdistrict Cooperatives using lectures, discussions, pre-tests, and post-tests consisting of 20 questions. The results showed a significant increase from an average pre-test score of 81.94 to a post-test score of 92.55 (an increase of 12.96%), proving the effectiveness of the training in strengthening knowledge about the duties, regulations, and management of cooperatives. This intervention addressed the information gap, increased member participation, and supported the economic independence of the village. Overall, the training became a sustainable foundation for the Red and White Subdistrict Cooperatives to realize inclusive economic growth in line with the national vision, with recommendations for further training for other administrators.